A wide temperature range dual-mode luminescence thermometer based on Pr3+-doped Ba(Zr0.16Mg0.28Ta0.56)O3 transparent ceramic. Issue 42 (14th October 2021) - Tang, Wei; Zuo, Chuandong; Li, Yingkui; Ma, Chaoyang; Yuan, Xuanyi; Wen, Zicheng; Cao, Yongge
Abstract : Compared to glasses and single crystals, transparent ceramics present extraordinarily large resistance to thermal shocks. Here, dual-mode LIR/FL temperature detection with a wide temperature range is realized with BZMT:Pr 3+ transparent ceramic. Abstract : Owing to the impact of robust thermal quenching, lanthanide-based luminescence thermometer operation can usually only be achieved within a comparatively small temperature scope (ambient temperature to 800 K). Here, this study presents a method for addressing the mentioned limits, and a luminescence thermometer with an ultra-wide temperature range has been achieved, which adopted Pr 3+ -doped Ba(Zr0.16 Mg0.28 Ta0.56 )O3 transparent ceramic to be the optical temperature probe. Based on the high luminescence intensity and excellent thermal stability of the 3 P0 – 3 F2 hypersensitive transition of Pr 3+ in Ba(Zr0.16 Mg0.28 Ta0.56 )O3 transparent ceramic, the intensity ratio of the emissions at 624 nm and 649 nm was employed for temperature sensing in an ultra-wide range (293–873 K), and the maximal relative sensitivity reached 1.05% K −1, outperforming most existing luminescence temperature measurement transparent ceramics. Furthermore, in Pr 3+ -doped Ba(Zr0.16 Mg0.28 Ta0.56 )O3 transparent ceramic, the lifetime of the 3 P0 – 3 H4 transition also exhibits prominent optical thermometry performance (303–873 K). The results presented in this work may be of high significance for the design of novel ratiometric/lifetime dual-mode optical temperature sensors in the high-temperature measurement field.